Meningkatkan Hasil Belajar Sepak Takraw Melalui Pendekatan Permainan Jala Hip Hop Siswa Kelas V SD Negeri 2 Sabungan Nihuta Kecamatan Ronggurnihuta Kabupaten Samosir Tahun Pelajaran 2017/2018 - Paodor Siburian (STMIK Budi Darma, 2021)
The background of this problem is that there are still many students who are not interested enough so that they are not serious in learning Sepak Takraw activities, this causes learning outcomes that are not optimal in playing Sepak Takraw. The formulation of the problem in this study is how to improve the learning outcomes of class V SD Negeri 2 Sabungannihuta, Ronggurnihuta District, Samosir Regency Academic Year 2017/2018. Classroom Action Research was carried out with the aim of knowing the increase in learning outcomes of Sepak Takraw through the hip hop mesh game approach in Class V SD Negeri 2 Sabungannihuta, Ronggurnihuta District, Samosir Regency, 2017/2018 Academic Year. This study uses a classroom action research method. The object of the research was through the hip hop net game method, while the subject was the fifth grade students of SD Negeri 2 Sabungannihuta, Ronggurnihuta District, Samosir Regency. The meeting in this study was designed in two cycles, namely cycle 1 and cycle 2. The instruments used in data collection were obtained from the performance test results displayed by the students at the time of the test. From the results of the research conducted, there was an increase in student learning outcomes from the initial conditions to cycle I and cycle II, both from the increase in the average value of hip hop-based football learning and the value of learning completeness. The average value of the initial condition was 59.79%, the average of the first cycle was 75.14% and the average of the second cycle was 87.29%, so that the increase from the initial condition to the second cycle was 27.50%. Improved soccer skills in hip hop learning takraw nets can be seen from the KKM value (75.00) or complete of 57.14% after action is taken in cycle I student learning scores that are complete are 8 out of 14 students and in cycle II all students complete declared as 100% complete.Keywords: Learning, Hip Hop Net, Sepak Takraw, Games